Regionalization of the Atmospheric Dust Cycle on the Periphery of the East Antarctic Ice Sheet Since the Last Glacial Maximum. (28th September 2018) - Baccolo, G.; Delmonte, B.; Albani, S.; Baroni, C.; Cibin, G.; Frezzotti, M.; Hampai, D.; Marcelli, A.; Revel, M.; Salvatore, M. C.; Stenni, B.; Maggi, V.
Abstract: Ice cores from inner East Antarctica provided some of the longest and most detailed climatic reconstructions and allowed understanding the relationships between atmospheric mineral dust and climate. In this work we present synchrotron radiation X‐ray Fluorescence geochemical data of dust from the TALDICE ice core drilled at Talos Dome, a peripheral ice dome of East Antarctica (Western Ross Sea). Results highlight a dominant southern South American origin for dust at TALDICE during the Last Glacial Maximum, similarly to other sites located further inland onto the polar plateau. On the contrary, a different scenario concerns Talos Dome during the Holocene if it is compared to more inner sites. The tight connection between high southern latitudes and Antarctica that characterizes cold climate stages becomes weaker since the onset of the last climatic transition and throughout the Holocene. The net effect of this process at Talos Dome is a modification of the atmospheric and environmental settings, owing to local Antarctic sources of Victoria Land to gain importance and become the dominant ones. At the same time in inner East Antarctica the provenance of dust remains remote also during Holocene, revealing an evolution of the homogeneous scenario observed in glacial periods. The enhanced sensitivity of peripheral ice sheet sites to local dust sources makes Talos Dome an ideal site to assess the climatic and atmospheric changes of the peripheral sectors of East Antarctica during the current interglacial period. Plain Language Summary: During the Last Glacial Maximum, about 20, 000 years ago, mineral dust from South America was massively transported toward Antarctica as a consequence of impressive environmental and climatic changes. Many ice cores drilled from the inner sectors of the Antarctic ice sheets support this scenario. Little is known when attention is shifted to peripheral areas and to interglacial periods. A new record of mineral particles at Talos Dome, a peripheral area of the East Antarctic ice sheet (Western Ross Sea sector), is here presented to partially close these gaps. Combining the data about concentration, composition, and grain size of the dust deposited at Talos Dome, it was possible to appreciate the influence played by local Antarctic dust sources to the depositional budget of the site. These local sources, corresponding to localized ice‐free areas, are extremely important when attention is given to the peripheries of the ice sheets. This is particularly true for interglacial periods, when the transport and the deposition of mineral dust from South America to Antarctica is much reduced. Key Points: The dust cycle reacted differently to the last climatic transition in different regions of the East Antarctic Ice Sheet The reduced transport of remote dust enhanced the emergence of a signal related to local dust dynamics in the Talos Dome ice core The chemical index of alteration provides constraints to track ice core dust provenance, also in relation to its formation environment